Contribution to the History of Cantillon by Henry Higgs (Quarterly Journal of Economics, 1891)
Contribution to the History of Cantillon by Henry Higgs Get access The Quarterly Journal of Economics, Volume 6, Issue 1, October 1891, Pages 94–95, https://doi.org/10.1093/qje/6.1.94-a Published: 01 October 1891